Hydrogeochemical Characterization and Appraisal of Groundwater Quality in Yisr River Catchment, Blue Nile River Basin, Ethiopia, by Using the GIS, WQI, and Statistical Techniques - Abebaw Demelash; Abunu Atlabachew; Muralitharan Jothimani; Abel Abebe (Journal of Chemistry)
Groundwater is a primary drinking, agricultural, domestic, and nondomestic water source in Ethiopia’s Yisr River watershed of the Blue Nile River basin. There has been no systematic investigation of the hydrogeochemical properties of groundwater in the research area. The study investigated the hydrogeochemical parameters of groundwater in the catchment to find out if it is fit for drinking and irrigation. A total of 26 samples of groundwater were collected and analyzed for seventeen parameters, including pH, temperature, EC, TDS, TH, K+, Na+, Ca2+, Mg2+, Fe2+, Cl−, HCO3−, CO32−, SO42−, F−, PO42−, and NO3−. The data were processed and evaluated using integrated hydrogeochemical techniques, including individual ionic signatures, interionic ratios, and multivariate statistical methods, such as multiple correlation analysis, principal component analysis, and hierarchical cluster analysis. The water quality index (WQI) and Na%, PI, RSC, SAR, EC, TDS, and MH were used to judge the quality of water for drinking and irrigation, respectively. The box plot diagram shows the dominant ions in descending order of Ca2+ > Mg2+ > Na+ > K+ and HCO32− > Cl- > SO42− > NO3− > F− for cations and anions, respectively. The chemical composition of shallow wells and springs indicates freshwater. At the same time, the deep groundwater wells are brackish. The two-factor loadings (principal component analysis) were used to explain the existence of anthropogenic and geogenic sources. Three clusters are identified in the dendrogram. The third cluster has the most significant linkage distance among all the clusters. This means that the groundwater sample in this cluster is geochemically different from the other two clusters, and that this cluster is made up of only deep wells. Water quality indices showed that water quality ranged from excellent to very poor, with the majority (53.85%) being excellent and 26.9% being good. The results of the calculated indices for agricultural water quality indicated that the water quality in most collected samples was in the good and excellent categories; however, the EC, RSC, MH, and TDS indices in deep groundwater wells were found to be hazardous. The findings of this study are useful for understanding groundwater sustainability for various reasons. However, they are also helpful in supporting water management and protection in the future.